Enhanced infectivity of herpes simplex virus type 1 viral DNA in a cell line expressing the trans-inducing factor Vmw65. - Werstuck, G (1990)
Vmw65 is a structural component of herpes simplex virus (HSV) which is involved in transactivating the expression of the viral immediate-early (IE) genes. To gain further insight into the function of this protein, a cell line, BSV65, was established which expresses biologically active Vmw65 under control of the Moloney leukemia virus long terminal repeat. This cell line was shown to specifically activate IE genes as demonstrated by transient transfection assays with reporter genes linked to HSV IE or delayed-early promoter-regulatory regions. Furthermore, by using mobility shift assays, cell extracts were shown to be capable of forming a Vmw65-containing complex with oligonucleotides that contained a TAATGARAT motif, a conserved cis-acting IE regulatory element which is required for Vmw65-mediated trans induction. BSV65 cells were able to complement HSV type 1 in 1814, a mutant which is unable to trans-induce IE gene expression and whose growth is impaired at low multiplicities of infection. Transfection of purified HSV type 1 viral DNA into BSV65 cells resulted in an approximately 200-fold increase in virus production compared with the parental cell line. In addition, in comparison to wild-type cells, infectious virus production occurred sooner and efficiency of plaque formation was higher in BSV65 cells following transfection of viral DNA but not following infection with virus. Northern (RNA) dot blot analysis of cells transfected with viral DNA showed that transcription of the IE gene Vmw175 was approximately 10-fold greater in BSV65 cells compared with wild-type cells. These results indicate that, in the presence of functional Vmw65, there is a greater probability that transfected viral DNA will lead to a productive infection.